2014
DOI: 10.1371/journal.pone.0107371
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Clinical Vibrio parahaemolyticus from 17 Coastal Countries, Determined through Multilocus Sequence Analysis

Abstract: Vibrio parahaemolyticus is a leading cause of food-borne gastroenteritis worldwide. Although this bacterium has been the subject of much research, the population structure of clinical strains from worldwide collections remains largely undescribed, and the recorded outbreaks of V. parahaemolyticus gastroenteritis highlight the need for the subtyping of this species. We present a broad phylogenetic analysis of 490 clinical V. parahaemolyticus isolates from 17 coastal countries through multilocus sequence analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
6
18
0
Order By: Relevance
“…In particular, recA presented the greatest number of polymorphic nucleotide sites (56) and a high degree of nucleotide diversity (0.0209), although it was slightly lower than dtdS (0.0224) (Table ). This result was similar to a previous study that identified highly divergent recA alleles and this locus had the greatest influence on the phylogenetic relationships (Han et al., ).…”
Section: Resultssupporting
confidence: 92%
“…In particular, recA presented the greatest number of polymorphic nucleotide sites (56) and a high degree of nucleotide diversity (0.0209), although it was slightly lower than dtdS (0.0224) (Table ). This result was similar to a previous study that identified highly divergent recA alleles and this locus had the greatest influence on the phylogenetic relationships (Han et al., ).…”
Section: Resultssupporting
confidence: 92%
“…The remaining 2 loci, recA and rpoB had 99 and 102 sites, respectively, suggesting recombination was evident and representing a significant source of genetic diversity in E. faecalis. High diversity in recA alleles and evidence for frequent recombination at this locus has been observed in previous studies (Han et al, 2014). In general, the allelic diversity of all 5 genes was less than 25%, indicating that the MLST design was balanced and corresponded with accepted designation principles (Maiden, 2006).…”
Section: Discussionsupporting
confidence: 66%
“…Among the seven genes analyzed, fumC and gyrB presented the highest degree of nucleotide diversity (0.03886 and 0.03075) and the greatest number of polymorphic nucleotide sites (137 and 139), suggesting that fumC and gyrB have much greater influences on the apparent evolutionary classification of human DEC. Together with the study by Han et al on Vibrio parahaemolyticus (recA dominant), this research helps us to understand the evolutionary relationships of these pathogens (Han et al, 2014). Previous MLST studies have confirmed recombination as a significant source of genetic diversity in DEC populations (Wirth et al, 2006).…”
Section: Discussionmentioning
confidence: 58%
“…Although there were differences between the results obtained from the eBURST algorithm and the ME tree, these two analytical tools each possess advantages. An eBURST analysis rapidly identifies CCs and their ancestral STs, while ME trees are superior in terms of revealing greater numbers of evolutionary relationships among different STs (Han et al, 2014).…”
Section: Discussionmentioning
confidence: 99%